The Analysis of Corporate Governance on Integrity Financial Statements in Banking Companies Listed on The Indonesia Stock Exchange - Devie, Devie; Anggono, Nathania Marchella Angelina; Pradana, Vincent Christian Satya; Kwistianus, Hendri (International Journal of Organizational Behavior and Policy, 2024)
The integrity of financial statements is often questioned due to manipulation of accounting data, involving directors, commissioners, audit committees, and company owners. This study empirically demonstrates the impact of corporate governance - through board size, independent commissioners, audit committees, and institutional ownership - on financial statement integrity. Using quantitative methods, the study involved 37 banking companies listed on the Indonesia Stock Exchange from 2017 to 2022. The results show that board size, independent commissioner, audit committee, institutional ownership, and leverage do not affect the integrity of financial statements, but firm size does.